Comparing effectiveness of adding prolonged trimetazidine or isosorbide dinitrate to beta-adrenoblocker therapy in stable angina patients - M. G. Glezer; M. V. Novikova; I. V. Kiseleva; R. T. Saigitov (Кардиоваскулярная терапия и профилактика)
Aim. To study effects of adding isosorbide dinitrate (ID) and trimetazidine MB 35 mg (Tr) to beta-adrenoblocker therapy in stable angina (SA) patients. Material and methods. In total, 40 patients with Functional Class II-III SA were examined. Combined therapy effectiveness was studied in a three-month randomized, open, comparative, parallel trial. Physical stress tolerance (PST) in treadmill test, angina attack incidence, nitrate dose, and health self-assessment dynamics (visual analogue scale) were assessed. Results. In both groups, PST increase by Month 1 was similar: 17% and 19%, respectively. Then PST stayed the same in ID group, and further increased in Tr group. By Month 3, PST in Tr group was twice as high as that in ID group: 15% and 34%, respectively. In Tr group, ST depression reduction, comparing to the baseline, was greater than in ID group: 49% vs 27%, respectively. It was associated with reduced angina attack incidence and need in short-acting nitrates. General health self-assessment improved by 20% (Month 1) and 35% (Month 3), comparing to 13% and 18% in ID group, respectively. Two participants dropped out of ID group, due to low medication tolerability (n=2), and myocardial infarction development (n=1). Conclusion. Comparing to ID, Tr demonstrated better tolerability profile, and long-run tolerance effect absence.